Reviews (Blackfriars, 1963)
Book Reviewed in this Article: THE UNITY OF CHRISTIANS, by Augustin Cardinal Bea, edited by Bernard Leeming THE CHURCHES AND CHRISTIAN UNITY, edited by R. J. W. Bevan secular religions in france 1815–1870, by D. G. Charlton TWENTIETH-CENTURY RELIGIOUS THOUGHT, by John Macquarrie THE GUITTON JOURNALS, 1952–1955, translated by Frances Forrest WILLIAM TEMPLE: SOME LAMBETH LETTERS 1942–1944, edited by F. E. Temple WILLIAM TEMPLE, ARCHBISHOP OF CANTERBURY: HIS LIFE AND LETTERS, by F. A. Iremonger DYNAMISME DE LA FOI ET INCROYANCE, par J. Loew et G. M. Cottier PROPOS SUR LA PREDICATION, par G. Michonneau et F. Vadon; Cerf L'OCCULTISME DEVANT LA SCIENCE, par Réginald Omez, o.P. DIABOLICAL POSSESSION, TRUE AND FALSE, by Jean Lhermitte, translated by P. J. Hepburne-Scott; Burns and Oates (Faith and Fact) BUDDHIST MONKS AND MONASTERIES OF INDIA, by Sukumar Dutt; Allen and Unwin